Newly diagnosed enhancing lesions: Steroid initiation may impede diagnosis of lymphoma involving the central nervous system. (November 2020) - Kam, Kwok-Ling; Brooker, Sarah M.; Mao, Qinwen; Barnea Slonim, Liron; Yaseen, Nabeel R.; Brat, Daniel J.; Sonabend, Adam M.; Lukas, Rimas V.
Highlights: Radiological characteristics of central nervous system lymphoma. Histological characteristics of central nervous system lymphoma. Histological characteristics of lymphoma with steroid effect. Administration of steroid prior to biopsy may affect diagnostic yield. Abstract: Establishing the pathologic diagnosis of central nervous system (CNS) lymphoma can be challenging, yet management of this potentially curable disease depends heavily on it. One avoidable impediment to obtaining an accurate and timely diagnosis is the pre-operative administration of steroids, which causes tumor involution and prevents appropriate sampling of viable tissue. We discuss a case of primary CNS lymphoma that highlights the evolution of the disease and the attempts to establish a diagnosis in the setting of prior administration of corticosteroids. Familiarity with these clinical scenarios will help others avoid delays in patient care that results from delayed diagnosis.